2020
DOI: 10.1038/s41598-020-80120-8
|View full text |Cite
|
Sign up to set email alerts
|

In-depth blood proteome profiling analysis revealed distinct functional characteristics of plasma proteins between severe and non-severe COVID-19 patients

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected over forty million patients worldwide. Although most coronavirus disease 2019 (COVID-19) patients have a good prognosis, some develop severe illness. Markers that define disease severity or predict clinical outcome need to be urgently developed as the mortality rate in critical cases is approximately 61.5%. In the present study, we performed in-depth proteome profiling of undepleted plasma from eight COVID-19 patients. Quantitative p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 45 publications
7
73
0
Order By: Relevance
“…Given the central role of proteins in biological processes as a whole, and in particular in diseases, we applied mass spectrometry–based proteomics to identify protein biomarkers that could discriminate between the COVID-19 patients who recovered and those who did not survive. Several proteomic studies ( 2 , 3 , 4 , 5 ) or even multi-omics studies, including proteomics ( 6 , 7 ), have to date investigated the serum or plasma of COVID-19 patients for the most part comparing a cohort of COVID-19 patients with control subjects (no disease) ( 2 , 3 ). Of special relevance to our work, an extensive study by Demichev et al ( 8 ) has already investigated the temporal aspect of COVID-19 progression in individuals to predict outcome and future disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Given the central role of proteins in biological processes as a whole, and in particular in diseases, we applied mass spectrometry–based proteomics to identify protein biomarkers that could discriminate between the COVID-19 patients who recovered and those who did not survive. Several proteomic studies ( 2 , 3 , 4 , 5 ) or even multi-omics studies, including proteomics ( 6 , 7 ), have to date investigated the serum or plasma of COVID-19 patients for the most part comparing a cohort of COVID-19 patients with control subjects (no disease) ( 2 , 3 ). Of special relevance to our work, an extensive study by Demichev et al ( 8 ) has already investigated the temporal aspect of COVID-19 progression in individuals to predict outcome and future disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have analyzed the serum or plasma proteome of COVID-19 infected patients (D’Alessandro et al ., 2020; Messner et al ., 2020; Park et al ., 2020; Shen et al ., 2020; Shu et al ., 2020). These were generally small-scale studies with single or few time points.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, 27 potential prognostic biomarkers (including complement factors, coagulation proteins, inflammation modulators, and pro-inflammatory factors induced by IL-6) were identified. Another study on serum proteome of patients with the severe and mild infections revealed differential expression of 91 proteins, of which 77 proteins were associated with neutrophil degranulation, blood coagulation, and neutrophil mediated immunity, and were proposed as prognostic biomarkers [ 101 ].…”
Section: Main Textmentioning
confidence: 99%